Cell Cytoskeleton Dynamics: Mechano-Sensing Properties - Borau, C.; Kim, T.; Kamm, R.; García-Aznar, J.M. (Jornada de Jóvenes Investigadores del I3A, 2012)
`The actin cytoskeleton network is the dominant structure of eukaryotic cells. It is highlydynamic and plays a central role in a wide range of mechanical and biological functions.Cytoskeleton is composed mainly of actin filaments (F-actin) resulting from the self-assemblyof monomeric actin (G-actin) and cross-linked by actin cross-linking proteins (ACPs) whosenature and concentration determine the morphological and rheological properties of thenetwork. These actin filaments are reversibly coupled to membrane proteins (critical to theresponse of cells to external stress) and in conjunction with motor proteins from the myosinfamily, are able to generate contractile force during cell migration. Knowledge of actincytoskeleton and its rheological properties is therefore indispensable for understanding theunderlying mechanics and various biological processes of cells. Here, we present a 3-DBrownian dynamics (BD) computational model in which actin monomers polymerize andbecome cross-linked by two types of ACPs, forming either parallel filament bundles ororthogonal networks. Also, the active and dynamic behaviour of motors is included. In thissimulation, actin monomers, filaments, ACPs, and motors experience thermal motion andinteract with each other with binding probabilities and defined potentials. Displacements aregoverned by the Langevin equation, and positions of all elements are updated using the Eulerintegration scheme.In this first part of the work, the mechano-sensing properties of active networks are investigatedby evaluating stress and strain rate in response to different substrate stiffness.